The Concept of an Ideal and Characterful Teacher According to the Perspective of Imam Al-Ghazali and Sheikh Az-Zarnuji and Its Relevance to Presidential Decree Number 87 of 2017 - Fitra Hamdani (al-Afkar, Journal For Islamic Studies, 2026)
Ideal and character-based teachers are an important foundation in shaping a quality generation, but the current moral crisis and decadence demonstrate the need for transformation in education and educators. Teachers, as the spearhead of education, are required not only to possess academic competence but also to be role models for students. This study aims to describe the views of the concept of ideal and character-based teachers according to Imam Al-Ghazali and Sheikh Az-Zarnuji, and analyze their relevance to the 18 character education values in Presidential Regulation Number 87 of 2017 concerning Strengthening Character Education. This research uses a qualitative method with a library research approach and philosophical analysis. Primary data sources include the book Ihya' Ulumuddin by Imam Al-Ghazali, the book Ta'limul Muta'allim by Sheikh Az Zarnuji, and a copy of Presidential Decree Number 87 of 2017. Secondary data include books, articles, journals, and other supporting written works. The data collection technique uses the documentation method, while data analysis is carried out using content analysis through the stages of description, comparison, and interpretation. The results of the study show that the concept of an ideal and characterful teacher according to Imam Al-Ghazali emphasizes the spiritual, moral, and intellectual dimensions of the teacher as a guide towards moral perfection (insan kamil). Teachers must have in-depth knowledge ('ilm), wisdom (hikmah), and the ability to purify the souls of students (tazkiyah). Meanwhile, Sheikh Az-Zarnuji in his book Ta'limul Muta'allim emphasizes the practical and methodological aspects of the learning process, where the ideal teacher is a figure who has moral integrity, pedagogical competence, and the ability to create a conducive learning environment. Comparative analysis shows that both figures have similarities in emphasizing the importance of teacher moral character, but have different emphases in learning approaches. Imam Al-Ghazali emphasizes the spiritual-Sufi dimension more, while Sheikh Az-Zarnuji focuses more on the practical-methodological aspect. The relevance of the concept of ideal and character teachers from both figures to Presidential Decree Number 87 of 2017 shows significant conformity with 18 character values which include: religious, honest, tolerance, discipline, hard work, creative, independent, democratic, curiosity, national spirit, love of the homeland, respect for achievement, friendly/communicative, love of peace, love of reading, care for the environment, care for society, and responsibility. This research contributes to providing a theoretical and philosophical basis for the development of the concept of an ideal and character-based teacher that is sourced from classical Islamic intellectual treasures and is relevant to the context of contemporary character education. These findings can be used as a reference in the preparation of teacher competency standards that are not only oriented to the technical pedagogical aspects, but also to the formation of character and moral integrity of teachers as character educators.